Application progress of Raman spectroscopy technology in the study of microbial cell metabolism dynamics - CHEN Yuchuan, QIN Liyao, JIANG Mingguo, WU Renzhi (Zhongguo niangzao)
Raman spectroscopy is a spectroscopic analysis technique based on Raman scattering, which has the advantages of high efficiency, non-contact, and real-time performance. It is commonly used in microbiological research for physiological and biochemical analysis of microbial cells. The advantages of Raman spectroscopy in microbial cell analysis was briefly introduced, its application in the study of fungi (yeast, pathogenic fungi), bacteria (spore-producing bacteria, pathogenic bacteria), and microalgae cells were mainly summarized, and the future development direction of Raman spectroscopy analysis technology was prospected. It provided new ideas for in-depth development and utilization of microbial resources, rapid classification and identification of microorganisms, and breeding.